Optimizing Production Costs by Redesigning the Treatment Process of the Industrial Waste Water. (2016) - Boer, Jozsef; Blaga, Petruta
Abstract: This paper aims at presenting a solution for the treatment of industrial waste water, resulted from the process of chemical pretreatment in the electrostatic painting industry, which can also supply water decontamination, thus preventing environmental destruction. The proposed technological process can be optimized by redesigning the pretreatment process by changing the path of the waste water and redirect it in the system created within the company, based on the observations noted during two years of sampling and testing. The results have been confirmed by the fact that through the implemented system, the waste water, can be efficiently cleaned and re-entered in the work process without affecting the quality of the process the pretreated products. By using this system lower production costs were achieved. This was possible by reducing the amount of water used from the distribution network, as well as by reducing the amount of chemicals needed for the pretreatment of contaminated water.